2014
DOI: 10.1371/journal.pone.0094845
|View full text |Cite|
|
Sign up to set email alerts
|

The Relationship between Serum Insulin-Like Growth Factor I Levels and Ischemic Stroke Risk

Abstract: ObjectiveThe aim of the study was to assess the relationship between insulin-like growth factor I (IGF-I) serum levels and acute ischemic stroke (AIS) in a Chinese population.MethodsAll consecutive patients with first-ever AIS from August 1, 2011 to July 31, 2013 were recruited to participate in the study. The control group comprised 200 subjects matched for age, gender, and conventional vascular risk factors. IGF-I serum levels were determined by chemiluminescence immunoassay. The National Institutes of Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…Several epidemiologic studies have reported an inverse relation between plasma IGF-1 levels and risk of ischemic stroke [11][12]. Similarly, Dong et al [13] found that lower IGF-1 levels were significantly related to risk of stroke, independent from other traditional and emerging risk factors in one cohort Chinese patients. Interesting, Selvamani et al [14] found that low-normal levels of IGF-I was associated with increased mortality in ischemic heart disease and stroke.…”
Section: Introductionmentioning
confidence: 91%
“…Several epidemiologic studies have reported an inverse relation between plasma IGF-1 levels and risk of ischemic stroke [11][12]. Similarly, Dong et al [13] found that lower IGF-1 levels were significantly related to risk of stroke, independent from other traditional and emerging risk factors in one cohort Chinese patients. Interesting, Selvamani et al [14] found that low-normal levels of IGF-I was associated with increased mortality in ischemic heart disease and stroke.…”
Section: Introductionmentioning
confidence: 91%
“…Extensive numbers of clinical studies have shown that lower IGF-1 levels significantly increase the risk of stroke and higher IGF-1 levels are associated with improved stroke outcomes, suggesting the circulating IGF-1 level may be used as a predictive value for ischemic stroke outcome (De Smedt et al 2011; Dong et al 2014; Tang et al 2014) and post-stroke IGF-1 treatment may be beneficial to both sexes. However, a recent study using miRNA that regulate IGF-1 found sex differences in the efficacy of this treatment.…”
Section: Sex Differences In Treatment Efficacy In Preclinical Studiesmentioning
confidence: 99%
“…It is produced mainly by the liver in response to the endocrine growth hormone stimulus; its bioavailability is regulated by IGF-binding proteins [107, 108], and its actions are mediated by specific membrane receptors, abundantly expressed in the brain [108]. During the normal aging process, IGF-1 levels decline and low IGF-1 levels have been correlated with frailty and decrease in cognitive abilities [111].…”
Section: Igf-1 Animal and Human Datamentioning
confidence: 99%
“…Epidemiologic studies in humans have reported an inverse relation between plasma IGF-1 levels and risk of ischemic stroke [128] Serum IGF-1 levels decline with age, lack of exercise, and in metabolic syndrome, and a low IGF-1 level is independently associated with increased risk of stroke [107]. Low circulating IGF-1 levels are associated with worse outcome after stroke [129, 130] although this correlation should be interpreted cautiously and not taken to necessarily imply a causative link.…”
Section: Igf-1 Animal and Human Datamentioning
confidence: 99%